Inovasi Pembuatan Sabun Padat Transparan Berbasis Minyak Kelapa Murni dengan Menggunakan Ekstrak Kulit Buah Naga sebagai Antioksidan - Munawwarah, Munawwarah; Adriana, Adriana; Irwan, Irwan (Jurnal Teknologi, 2024)
This study aims to examine the effect of the volume of dragon fruit peel extract and NaOH on moisture content, pH, free fatty acids, free alkali and antioxidant activity in the resulting soap products. This research utilizes virgin coconut oil and dragon fruit peel extract. Dragon fruit skin contains various bioactive compounds such as polyphenols, vitamin C, vitamin E, vitamin A, alkaloids, terpenoids, flavonoids, thiamine, niacin, pyridoxine, cabolamine, phenolics, carotene and phytoalbumin so that it has pharmacological effects as an antioxidant. The independent variables used are variation of dragon fruit peel extract 0 mL, 2 mL, 4 mL, 6 mL, 8 mL, and variation of NaOH volume 12 mL, 14 mL, 16 mL. The tests carried out include pH test, water content test, free fatty acid test, free alkali test, antioxidant activity test using DPPH method, and organoleptic test. The results obtained the best transparent solid soap with the composition of dragon fruit peel extract 2 mL and NaOH 12 mL with pH 9.2, water content 11.21%, free fatty acids 1.394%, free alkali 0.368%. Antioxidant activity test was analyzed using UV-Vis Spectrophotometer. The analysis results showed the presence of antioxidant activity which is classified as strong at 46.23%. Based on the data obtained, it can be concluded that the transparent solid soap produced has reached the Indonesian National Standard (SNI).